IMPLEMENTATION OF SMART (CERDAS) SCHOOL PROGRAM OF MUHAMMADIYAH DISASTER MANAGEMENT CENTER (MDMC): THE CASE STUDY OF THE SMP MUHAMMADIYAH 1 SURAKARTA 2017/2018 - Istanto, Istanto; Ayiyah, Siti Nur (Muhammadiyah University Press, 2018)
CERDAS School is one of new programs implemented in school learning. This program is important and very useful to be implemented in schools considering its excellent orientation and output for students and teachers of Islamic Religious Education and Counseling Guidance. The purpose of the CERDAS School Program is that the schools will have knowledge, skills and policies to respond to the risks of natural disasters or human-induced disasters (bullying/violence at school) and becoming agent of peace and reconciliation. The program was implemented and delivered through learning and training that were set as game in each of material delivery. In learning, CERDAS school materials were inserted in Akhlaq subject and counseling guide, while the training was held to equip and train representatives of school peace. This research was of field research and data was collected by using observational data record, interview and documentation that can support the research study. The data was analyzed by using deductive model. Findings of the research indicated that 1) Implementation of CERDAS School Program of Muhammadiyah Disaster Management Center (MDMC) in SMP Muhammadiyah 1 Surakarta was quite successful in changing the way and attitude of learners to become agents of peace for themselves and others at the school. It was seen since the implementation of CERDAS School Program that learners with advantages were not showing arrogant attitude, but they can be humble. Likewise, those who had some inferiority were not feeling inferior with their shortcomings. In fact, the shortcoming was a whip to be more eager to appreciate God's blessings. With the CERDAS School Program, learners know how to make peace with themselves, barriers to the peace, and find a way to the peace. 2) Implementation of TANDUR method in Smart School Program of SMP Muhammadiyah 1 Surakarta can be conducted during Training of CERDAS School Representatives through Wisdom Word, introduction to and core of learning, model and practice and action. While, the TANDUR method was delivered duringschool hours in core of learning only.